Effects of vibro-milling time on phase formation and particle size of Zn3Nb2O8nanopowders - A. Prasatkhetragarn (2018)
A monoclinic phase of zinc niobate, Zn3Nb2O8, nanopowder was synthesized by a solid-state reaction via a rapid vibro-milling technique. The effect of milling time on the phase formation and particle size of Zn3Nb2O8powder was investigated. The formation of the Zn3Nb2O8phase in the calcined powders has been investigated using DTA and XRD techniques. Morphology, particle size and chemical composition have been determined via a combination of SEM and laser diffraction techniques. It was found that an average particle size was achieved at 20 h of vibro-milling after which a higher degree of particle agglomeration was observed on continuation of milling to 30 h. In addition, by employing an appropriate choice of the milling time, a narrow particle size distribution curve was also observed. © 2010 Elsevier B.V. All rights reserved.